Boussineq Problem for Elastic Half-Space Reinforced with Fibres in Vertical Direction - Świtka, R. (Engineering Transactions, 1996)
Solution of Boussinesq problem has been given in the paper for the particular case of the fibrous composite half-space. The continuous medium has been assumed to consists of the matrix reinforced with vertical elastic fibres. The theory of fibrous composites proposed in [10] is used. The results obtained are compared with the Boussinesq formulae. It has been found that the fibrous phase takes over most of the forces transmitted through the half-space.